Turning German Steel Production Green: Quantifying Diffusion Scenarios for Hydrogen-Based Steelmaking and Policy Implications - Philipp Preis (Junior Management Science (JUMS), 2023)
The German steel industry is in jeopardy. Current steel production must be comprehensively transformed to achieve the emission targets imposed by the Federal Climate Change Act. A promising alternative that has increasingly gained momentum in recent years is hydrogen-based steel production. This thesis analyzes the potential of this method to transform the German steel industry. First, drivers that will decisively influence the future role of hydrogen-based steelmaking are identified. Subsequently, these drivers are linked in a quantitative model to develop explorative diffusion scenarios and to draw conclusions for policymaking. Four representative scenarios are extracted and analyzed. Large differences between the scenario outputs illustrate that the diffusion of hydrogen-based steelmaking is subject to significant uncertainties. It becomes clear that the most effective lever for promoting the attractiveness of hydrogen-based steelmaking is increasing the cost of conventional production by exposing it to CO2 prices. However, such exposure simultaneously suggests disadvantages towards producers that are not subject to this regulation. To mitigate the emerging risk of carbon leakage effects, suitable policy measures are required.
Keywords: 650; Green steel; Green hydrogen; Energy transition; Energy policy